310 Impact of Obesity on Morbidity Associated With Endoscopic Spine Surgery. (1st April 2022) - Bergquist, Julia; Greil, Madeline; Hofstetter, Christoph P.
Abstract : INTRODUCTION: Obesity has profound impact on traditional spine surgery and is associated with increased surgical complexity and postoperative complications. METHODS: A retrospective review of a single-surgeon database was conducted for all adult patients undergoing unilateral laminotomies for bilateral decompression between November 2015 and March 2021. Data collected included operating room induction time, procedure time, length of hospital stay, use of analgesics, post-operative complications, post-operative pain reduction measured by visual analogue scale (VAS), and quality of life measured by EQ-5D-5L and Oswestry Disability Index (ODI). For statistical analysis, patients were categorized into non-obese and obese groups as defined by the World Health Organization based on body mass index (BMI, kg/m 2 ): 18-29.9 and 30+. Data between groups were compared using Kolmogorov-Smirnov test. Recovery complications, analgesics use, and need for same-level revision were assessed using logistic regression. RESULTS: Our patient cohort included 181 patients with an average age of 63.5 years. Patients with higher BMI suffered more pronounced back pain disability (P < 0.01) preoperatively. Operative details including number of segments operated on were similar within our cohort. Surgical induction times increased significantly with BMI (Pearson correlation 0.228, P < 0.01), while procedure times were not affected. Mean follow-up was 22.8 +/-1.4 months. There were no differences between obese and non-obese patient populations' low-level analgesic use at two weeks post-operation, need for revision, and degree of VAS, ODI, and EQ-5D-5L improvement. However, there were significant positive correlations between BMI and length of hospital stay (P < 0.009), two-week post-operative narcotic use (P = 0.001), and postoperative complications (P = 0.027). CONCLUSION: Working channel endoscope can mitigate some procedural challenges related to obesity, however, the obese patient population requires increased health care resources and suffers from more frequent postoperative complications.